EFFECTIVENESS MODEL DISCO-NING JS LEARNING AND LEARNING MODEL ON THE IMPROVEMENT OF COMPETENCE STAD conic CLASS (Universitas Negeri Semarang, 2017)
The development of learning devices with Disco-Ning JS model is expected to make a better learning. This is a developmental research. This model uses a modified 4-D model by Thiagarajan, Semmel and Semmel. The subjects are the students of XI Science Class of SMA Negeri 1 Demak in the academic year of 2016/2017. The developed devices are valid with the validation analysis of learning devices on conic sections material covering the syllabus, lesson plan, BPD, LKPD, and student achievement test. Data collection was gathered through testing and observation. Test data were processed with learning mastery test and average deviation test. The result showed: (1) The results of expert validation shows that syllabus obtained an average score of 3.92 with good criteria, lesson plan obtained an average score of 3.72 with good criteria.; (2) The implementation of the valid Disco-Ning JS learning device was proven effective because it meets thoroughly classical passing standardization of 75%, the average learning achievement in the class taught by a Disco-Ning JS model was better than a class taught by STAD, and the observation of character values including creativity, independence, hard-work, and curiosity of 36 students displayed 17% in the category of have not seen (BT), 78% in the category of began to develop (MB), and 6% in the category of entrenched (MK). The conclusion obtained from this research is the mathematics learning devices developed with the model of Disco-Ning JS on conic sections material of class XI is valid, effective, and practical. The above research also showed that the learning model of Disco-Ning JS is eligible to be practiced in mathematics subject in high schools and can be developed for learning on the conic sections.